EVALUATION AND CLASSIFICATION OF MOTOR DEVELOPMENT; SPAWNING PROJECT PARTICIPANTS OF UNIVERSITY OF SANTA CRUZ DO SUL – RS (Fiep Bulletin - online, 2016)
This work aims at presenting the motor profile of participating students Spawning Project - "Swimming For Handicapped" intencionista project of the University of Santa Cruz do Sul - UNISC / APAE, acting for 30 years, serving students from more different pathologies. The project goal is to promote activities in the liquid medium so that the students increase their repertoire psychomotor and attitudes in the water and out of it when possible too. This research aims to assess the motor profile of participants Spawning Project in 2014 (1) March and reassessed in 2014 (2) October. The study gathered 9 students with Mental Disabilities, of both sexes, aged from 04 to 15 years. Mobility Thin and Global Spatial Organization and Temporal Organization: pre and post tests of Motor Development Scale (EDM), which comprise the following aspects were applied. With the results that it has contacted the fine motor deficit students presented the results in the global motor function evaluated showed satisfactory results and lower, Spatial Organization and achieved good results, and below the latter aspect assessed Temporal Organization showed satisfactory results, the comparison of motor age among participants Spawning Project showed that after the intervention participants had significant improvement. The results of this study reveals that the Aquatic activities is an effective alternative for promoting improvements in motor development. Thus, according to this study, where students were assessed individually, so one can trace an individualized treatment.
Keywords: .